TINJAUAN KRIMINOLOGI TERHADAP TINDAK PIDANA PENIPUAN JUAL BELI ONLINE - Susanto, Wahyu Adi; Hendrawati, Heni; Basri, Basri (Fakultas Hukum Universitas Muhammadiyah Magelang, 2017)
This study discusses the overview of Criminology Crime Against Scams Buy Sell Online. Who in real life is very rife due to the lack of security and surveillance conducted by public authorities, so that many victims of criminal fraud and selling online, supported and easy to commit a criminal act of buying and selling online with a variety of modes available. To resolve the problem it should be known what are the factors that caused the criminal act of buying and selling online in terms of criminology. And how do the efforts of law enforcement officers in dealing with criminal fraud and selling online. Writing of this method normative empirical research that aims to make the data in a systematic, factual, and accurate about the facts and what happens on the field sebenrnya. With a data sekuder and as a source of primary data. Factors that cause the Crime Fraud Buy Sell Online influenced by various factors such as economic factors, environmental factors, social and cultural factors, factors easily commit crimes of fraud and selling online, factor the lack of risk of being caught by